Effect of pickling process on adhesion strength of ti oxide layer on titanium alloy substrate - Izman, Sudin (Trans Tech Publications, 2011)
Titanium alloys are commonly used in biomedical application in hard tissues replacement especially for knee and hip implants. Surface modifications are required prior to diamond coating process for improving the tribological and wear properties of the titanium alloy. In this study, experiments were carried out to investigate the effects of different pickling times as well as temperature on the adhesion strength of oxide layer formed on the Titanium alloy after oxidation process. The aqueous acid solution of HF and HNO3 was used as a pickling solution. The chemical pretreatment was carried out at 4 levels by varying the pickling time as well as temperature. All treated samples were thermally oxidized in a fixed parameters at 900 °C for 25 hours. Surface morphology, oxide layer thickness and adhesion strength were measured after each step using FESEM and Blast Wear Tester (BWT). It was revealed that the thickness of oxide layer increases with pickling time but the adhesion strengths become weaker. It was also found that the adhesion strength of oxide layer formed on Ti substrate surface increases with the increase of temperature while the thickness of the oxide layer decreased within 40oC pickling temperature.